World Bank Group Climate Change Action Plan 2021-2025 : South Asia Roadmap - World Bank Group (World Bank, Washington, DC, 2021)
South Asia is one of the most vulnerable regions to climate change. The people of South Asia are living through a "new climate normal," where intensifying heat waves, cyclones, droughts, and floods are testing the limits of governments, businesses, and citizens to adapt. Jacobabad in Pakistan's Sindh province was, this year, the hottest city on the planet with temperatures higher than the human body can handle. In 2020, more than three million people were evacuated to safety from the fury of Super Cyclone Amphan. At the same time, South Asia has an unfinished development agenda with legitimate aspirations to reach middle income status in the foreseeable future, which will include increasing access to energy, increasing rural incomes and managing large scale urbanization, among others. The success with which South Asian countries navigate these development transitions, while also reducing emissions and increasing climate resilience, will determine the region's ability to lift millions from the threat of poverty and vulnerability, and help the world to secure the overall climate transition.